A Sociolinguistic Analysis Of Indonesian - English CodeMixing Found In Samsung Mobile Phone User Manual - Sukoraharjo, Ginanjar (2012)
This research paper analyzes code mixing found in Samsung mobile phone user manual. This study is analyzing 1) the forms of code mixing, and 2) the reasons of using code mixing. The type of this research is descriptive qualitative research. The data of this research are sentences containing code mixing in Samsung mobile phone user manual, especially on Samsung GT-S3653 Corby (2010) user manual which uses Indonesian, especially in the first 4 chapter of user manual they are: safety and usage information, introducing your mobile phone, assembling and preparing your mobile phone, and using basic function. In collecting data, the writer uses documentation method. The result of this research, the writer finds two findings, they are: first, he forms of code mixing. There are four forms of code mixing: they are 213 data of words or 61,9 %, 123 data of phrase or 35,75%, 5 data of hybrid or 1,45%, and 3 data of repetition word or 0,87%. Second, the reasons of using code mixing are prestige feeling motive 14 data or 4,06% and need feeling motive 330 data or 95,93%.